Development of a growth factor delivery system - Kirby, Giles T.S. (2014)
Bone repair is not always a spontaneous process. In some cases, intervention is required. This can involve the use of autograft but requires donor tissue. As a consequence there is a potential lack of material and donor site morbidity. Current alternatives are limited. There is a need for synthetic alternatives with a similar efficacy to autograft. Growth factors are currently being explored to address this need. A limiting factor to growth factor approaches are safety concerns and high costs. Both these problems stem from the fact that growth factors have short in vivo half lives and are administered at supraphysiological levels to maximise the duration of effect. There is a strong need for a growth factor delivery system that can maintain therapeutic doses and restrict administration to a specific location. This is currently limited by the fragile nature of growth factors.